Sound absorption performance of microperforated honeycomb metasurface panels with a combination of multiple orifice diameters. (15th January 2020) - Xie, Suchao; Wang, Da; Feng, Zhejun; Yang, Shichen
Highlights: MHMP is better sound absorption than MPPA at the same resonant frequency. MPP thickness and orifice diameter affect sound absorption bandwidth of the MHMP. The sound absorption effect of the combined MHMP is equivalent to a certain MHMP. The combined MHMP forms a hybrid resonance mode by coupling different resonators. Abstract: This study demonstrated a microperforated honeycomb metasurface panel (MHMP) with a micro-perforation on each honeycomb cell and designed an MHMP combining different orifice diameters. Based on two theoretical models ( i.e ., microperforated panel (MPP), and Helmholtz resonator (HR), models) and impedance tube testing, the sound absorption performance of MHMP was verified. Through impedance tube testing, the influences of orifice diameter and thickness of MPP on sound absorption performance of MHMP were assessed. The results demonstrate that the designed MHMP can absorb 99% of sound at its resonant frequency and conforms to the HR model. The MPP model proves that MHMP needs to be thinner to obtain better sound absorption effects at the same peak frequency of sound absorption compared with the MPP. With the increase of MPP thickness or decrease of orifice diameter, the resonant frequency of the MHMP decreases and the frequency band of sound absorption becomes narrower. The test results show that the sound absorption effects of MHMP with a combination of multiple orifice diameters being equivalent to those of MHMP with the mean value of the orifice diameters used in the combination. For example, sound absorption effects of MHMP combining orifice diameters of 0.5 and 0.7 mm are equivalent to those of MHMP with an orifice diameter of 0.6 mm. The HR model proves that the equivalent acoustic impedance of the combined MHMP is approximately equal to the mean value of acoustic impedances of an MHMP with different orifice diameters in the combination. In addition, the results show that such an equivalent phenomenon should be considered in the design of sound-absorption materials.